Longitudinal Clustering via Mixtures of Multivariate Power Exponential Distributions - Patel, Nidhi (My University, 2016)
A mixture model approach for clustering longitudinal data is introduced. The approach, which is based on mixtures of multivariate power exponential distributions, allows for varying tail-weight and peakedness in data. In the longitudinal setting, this corresponds to more or less concentration around the most central time course in a component. The models utilize a modified Cholesky decomposition of the component scale matrices and the associated maximum likelihood estimators are derived via a generalized expectation-maximization algorithm.
Keywords: longitudinal data; model-based clustering; mixture models; power exponential distribution